Impact of integrating large-scale DFIG-based wind energy conversion system on the voltage stability of weak national grids: A case study of the Nigerian power grid. (November 2021) - Adetokun, Bukola Babatunde; Muriithi, Christopher Maina
Abstract: This paper investigates the impact of integrating large-scale Doubly-Fed Induction Generator (DFIG)-based wind energy conversion system (WECS) on the voltage stability of the 52-bus, 330 kV Nigerian power grid. Indices derived from Active Power–Voltage (PV) and Reactive Power–Voltage (QV) analyses have been utilized to determine the voltage stability limits in terms of the maximum active power margin (APM) and minimum reactive power margin (RPM) of the system with the associated critical voltage-reactive power ratio (CVQR) of the system buses. Simulations have been done in DIgSILENT PowerFactory and the results analysed using MATLAB. This work also demonstrates the effectiveness of DFIG-based WECS in mitigating the overvoltage issues in the Northern region by ensuring that all bus voltages are within the acceptable limits of 1.0 ± 0.05 p.u. The results show that the optimal DFIG-based WECS penetration level (PL) that satisfies a bus voltage criterion of 1.0 ± 0.05p.u with the APM and CVQR not falling below their respective base case values and the loading of all critical power system equipment not exceeding 80% is 35%. Therefore, this work has demonstrated the possibilities of large-scale DFIG-based WECS as a viable solution for voltage stability improvement of a weak National grid while meeting the increasing energy demand. Highlights: Impact of large-scale DFIG-based WECS on the voltage stability of Nigerian power grid is carried out. Loading effects of DFIG-based WECS on the critical power system element is examined. The optimal DFIG-based WECS penetration level is determined. Large-scale DFIG-based WECS integration can improve voltage profile of Nigerian power system.